2020
DOI: 10.3389/fncel.2020.00226
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Vasodilators for the Treatment of Noise-Induced Hearing Loss: Are They Really Effective?

Abstract: We live in a world continuously immersed in noise, an environmental, recreational, and occupational factor present in almost every daily human activity. Exposure to high-level noise could affect the auditory function of individuals at any age, resulting in a condition called noise-induced hearing loss (NIHL). Given that by 2018, more than 400 million people worldwide were suffering from disabling hearing loss and that about one-third involved noise over-exposure, which represents more than 100 million people, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 66 publications
0
23
0
1
Order By: Relevance
“…Antioxidants protect against NIHL [ 24 , 25 ]. Diverse antioxidants, including N-acetyl-L-cysteine (NAC), acetyl-L-carnitine (ALCAR), 4-hydroxy alpha-phenyl-tert-butylnitrone (4-OHPBN), salicylate, 2,4-disulfonyl a-phenyl tertiary butyl nitrone (HPN-07), HK-2, and others, show protective effect against noise-induced damage in the cochlea [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants protect against NIHL [ 24 , 25 ]. Diverse antioxidants, including N-acetyl-L-cysteine (NAC), acetyl-L-carnitine (ALCAR), 4-hydroxy alpha-phenyl-tert-butylnitrone (4-OHPBN), salicylate, 2,4-disulfonyl a-phenyl tertiary butyl nitrone (HPN-07), HK-2, and others, show protective effect against noise-induced damage in the cochlea [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Jung et al, in their review study in the field of association between nutritional factors with hearing loss, found that various nutritional factors (such as vitamins A, C, and E, and zinc) are associated with hearing status, and the incidence of hearing loss was increased with the lack of these micronutrients 30 . Alvarado et al in their study showed that combination of some or all of the antioxidants, such as NAC, vitamins A, C, and E, and magnesium (Mg), can affect on their mechanisms of action, potentiating the optimistic effect over noise overexposure 31 …”
Section: Discussionmentioning
confidence: 99%
“…However, according to our search results, so far no study has been done to systematically review the relationship between vitamins/antioxidants on occupational NIHL. Only, Alvarado et al in their review on a small number of studies showed that combination of some or all of the antioxidants, such as NAC, vitamins A, C, E, and magnesium (Mg), can produce synergism and/or redundancy in their mechanisms of action, potentiating the positive effect over noise overexposure, and also considered these otoprotective agents as a hopeful new therapeutic strategy for ameliorating, delaying, or even preventing the impact of noise on hearing 31 . So, the current study is conducted to systematically review the protective effects of vitamins/antioxidants on occupational NIHL.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most animal studies investigating the effect of ALA on the cochlea have used drug-induced hearing loss models [ 10 , 11 , 14 , 15 ]. Acoustic trauma triggers inflammatory reactions, oxidative stress, and insufficient blood supply to the inner ear, leading to apoptosis of sensory cells [ 18 ]. Several antioxidants, such as glutathione and N-acetylcisteine, have been studied to target oxidative stress, and have been reported to have an oto-protective effect against NIHL [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%